THE RESEARCH OF SPORT EDUCATION MODEL IN PHYSICAL EDUCATION PROGRAM: A SYSTEMATIC LITERATURE REVIEW - Ginanjar, Shela; Samsudin; Rihatno, Taufik (STKIP Muhammadiyah Kuningan, 2024)
The purpose of this research is to see how the research that has been carried out regarding the sport education model in physical education learning is implemented at every level of education and discuss the views of teachers and parents. All the data discussed in this research is based on Scopus articles to be more reliable. The method used was a systematic literature review, where the search results found 396 Scopus-indexed articles from 1968–2024, which were selected systematically to become 77 articles relevant to the research question. Based on these results, there are several conclusions, according to this research: 1) Spain and the USA are the most dominant countries in the amount of research related to this sport education model, and further innovation is needed so that this sport education model can also be applied at the college and school level, on the basis of which it is felt that there is still a lack of research. 2) Sports Education Research This model of physical education learning mostly uses sports games, with a high dominance in the sports of basketball and volleyball. 3) Research on sport education models in physical education learning is known to involve many sophisticated media, such as videotaped, audiotaped, accelerometers, and software used for qualitative data processing. and 4) The Sport Education Model application itself combined with technology and social media makes parents actively involved in supporting learning so that the goals designed by the teacher are achieved and the students' parents feel satisfied with the results. Future research is expected to help sharpen studies that have not been revealed in the Sport Education Model research in physical education learning, such as cognitive, affective, and psychomotor aspects that have been widely carried out, and longitudinal research is needed regarding how this Sport Education Model can help shape students' strong character in physical education activities.